Ecosystem-based reference points under varying plankton productivity states and fisheries management strategies. (29th June 2019) - Guo, Chuanbo; Fu, Caihong; Forrest, Robyn E; Olsen, Norm; Liu, Huizhu; Verley, Philippe; Shin, Yunne-Jai
Abstract: In the context of ecosystem-based fisheries management, which should consider changing and uncertain environmental conditions, the development of ecosystem-based biological reference points (EBRPs) to account for important multi-species (MS) interactions, fishery operations, and climate change, is of paramount importance for sustainable fisheries management. However, EBRPs under varying plankton productivity states and fisheries management strategies are seldom developed, and the ecosystem effects of these changes are still largely unknown. In this study, ecosystem-based F MSY (fishing mortality rate at MSY) values were estimated within an end-to-end ecosystem model (OSMOSE) for three focused fish species (Pacific Herring, Clupea pallasii ; Pacific Cod, Gadus macrocephalus ; Lingcod, Ophiodon elongatus ) under three plankton productivity states of differing plankton biomass at high, current, and low levels. In addition, ecosystem effects were compared across different plankton productivity and fisheries management strategies with the latter consisting of two fishery scenarios (i.e. single-species-focused (SS) and MS-focused), various fishing mortality rates, and two harvest policies (with and without harvest control rules, HCRs). Main findings of this study include: (i) plankton productivity change affected the values of ecosystem-based F MSY, which increased as plankton productivity states changed from low to high plankton biomass; (ii) ecosystem-based F MSY for Pacific Herring and Pacific Cod stocks increased when fishery scenarios shifted from SS-focused to MS-focused; (iii) fisheries management incorporating HCR yielded more stable system catch and system biomass; and (iv) high plankton biomass combined with fisheries management using HCR could maintain stable ecosystem production and sustainable fisheries. Based on our findings, we highlight possible adaptive fisheries management strategies in the face of future climate and ocean changes. Overall, EBRPs complement SS stock assessments by incorporating key ecological processes and ecosystem properties, thus providing supporting evidence for better incorporation of ecosystem considerations into scientific advice for sustainable fisheries management.